Влияние добавок TiN, Mo, Ni на электросопротивление и прочность горячепрессованного нитрида кремния - Ивженко, В.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The influence of TiN, Mo, Ni additions on resistivity and strength of hot pressed silicon nitride has been investigated. Dense material based on silicon nitride with additives up to 30 % TiN and 1,7 % Mo (volume percents) was prepared. It has bending strength 450–500 MPa and specific resistivity~ 10-2 Ω·m. The behavior of material permits to manufacture of complex shape parts by spark cutting. The nickel addition has negative affect on strength of hot pressed silicon nitride.